Do physical activity interventions influence subsequent attendance and involvement in physical activities for children with cerebral palsy: a systematic review. Issue 9 (24th April 2022) - Kilgour, Gaela; Adair, Brooke; Stott, Ngaire Susan; Steele, Michael; Hogan, Amy; Imms, Christine
Abstract: Purpose: To investigate if children with cerebral palsy have sustained attendance and involvement in physical activities after completing physical activity interventions. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed. Seven databases were searched for the period 2001–2020 with hand-searching of pertinent reference lists. Criteria for study inclusion were participants aged 0–18 years and ≥50% with cerebral palsy; follow-up ≥1 month beyond completion of the physical activity intervention; and measurement of attendance and/or involvement in any physical activity post-intervention. Study selection, data extraction, and risk of bias assessments (Physiotherapy Evidence Database (PEDro) or tool for non-randomised studies) were completed independently by paired reviewers. Results were compiled by narrative synthesis. Results: Thirteen studies were included (11 randomised controlled trials (RCTs), two non-randomised case series; intervention sample sizes: 6–34). All study participants had cerebral palsy and were aged 4–16.7 years. PEDro scores for the RCTs ranged from 5 to 10; 10 did not blind one or more therapist, participant, or assessor. Two case series showed high risk of bias. Twelve studies reported on attendance, with positive changes in three studies. At 4–14 weeks post-intervention, two studies demonstrated positive changes were maintained. Four studies included involvement outcomes; one reporting positive changes in physical activity involvement four weeks after intervention completion. Conclusions: Physical activity attendance may be influenced by physical activity interventions in the short term, but more robust research designs are required to investigate whether gains can be sustained. Activity involvement, which may influence ongoing participation, is under-researched. Implications for Rehabilitation: Positive changes in attendance and involvement following physical activity interventions appear short term at best. Physical activity interventions should have longer follow-up periods to determine the effect on sustained physical activity participation. Careful selection and reporting of attendance and involvement outcome measures is required. The optimal physical activity intervention to increase attendance or involvement in physical activities remains uncertain.